PENGARUH KOMUNIKASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA SMK PELITA NUSANTARA 1 - 2 SEMARANG - Untung Widodo (STIE Pelita Nusantara Semarang, 2011)
In order to reach the organization’s objectives efficiently and effectively, high employee’s performance is needed by the organization. Timeliness or job discipline and communication are factors that influence on employee’s performance. Communication as a complex’pattern, and it’s relationship with human social life community. Individual relationship which is information interchange or the other informal communication was rarely happen, because lack of rellationship and different domicile. The other communication borders was found even any problems’ happen and need own management’s decision to optimalize the function of willingness, complain and employee’s aspiration, motivate the level of discipline, increase of comfortable communication and job satisfaction.